Internal time : chronotypes, social jet lag, and why you're so tired - Roenneberg, Till (Harvard University Press, 2012)
Internal Time combines storytelling with accessible science tutorials to explain how our internal clocks work--for example, why morning classes are so unpopular and why "lazy" adolescents are wise to avoid them. We learn why the constant twilight of our largely indoor lives makes us dependent on alarm clocks and tired, and why social demands and work schedules lead to a social jet lag that compromises our daily functioning. --from publisher description